An introduction to sustainable development - Elliot, Jennifer A (New York Routledge, 2013)
This fourth edition has been comprehensively rewritten and updated to provide a concise, well illustrated and accessible introduction to the characteristics, challenges and opportunities of sustainable development with particular reference to developing countries. The contested nature of sustainable development is explored through a detailed consideration of changing ideas and practices within environmentalism and development thinking. The text identifies the different actors involved (from institutions of global governance through to community based organisations), the policies and mechanisms through which sustainable development is being sought and considers the outcomes for particular groups and environments in both rural and urban contexts.
Includes bibliographical references and index
Keywords: Sustainable development -Developing countries